Insult as a Linguistic and Legal Phenomenon - Nikolaevna Ivanishcheva, Olga; Viktorovna Bolgova, Elena; Mikhailovna Shadrina, Irina; Vladimirovna Gushchina, Anna; Borisovich Nikonov, Sergey (International Journal of Engineering and Technology, 2018)
In the article, on the material of the texts of linguistic expertise on cases of insult, the main problems and ways of their solution in conducting forensic linguistic expertise of a case of insult in the courtroom are presented. It was stated that when conducting linguistic expertise of conflicting statements, it is not a verbal strategy of achieving the result that matters, but an attack on a person's honor, dignity, and business reputation. The need to include extralinguistic and pragmatic factors in the attention of linguistics expert is emphasized: the focus of insult on a particular person, gestures and the indication of part-of-speech characteristics of the analyzed word.Â Â